Paper for processing, paper for paper yarn, twisted yarn, textiles, pile for rugs, fabrics, and methods for manufacturing paper for processing.
Patent Information
- Application Number
- JP2025064646
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-22
Smart Images

Figure 2026170818000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to base paper for processing, base paper for paper yarn, twisted yarn, textiles, pile for carpets, fabrics, and a method for manufacturing base paper for processing. [Background technology]
[0002] Traditionally, in consideration of environmental issues, recycling issues, and resource conservation, there has been a demand for materials made from naturally derived materials such as plants, as an alternative to petroleum-based materials such as plastics. Pulp is an environmentally friendly material with advantages such as biodegradability and the absence of harmful substances when incinerated after disposal. Attention is being drawn to its use as a raw material for yarn and cloth, as well as as a substitute for plastic products made from paper, and as base paper for processing these materials.
[0003] For example, Patent Document 1 discloses a base paper for paper yarn that contains 1% to 100% by mass of fine fibrous cellulose with a fiber width of 20 nm to 1000 nm, and is treated to make it water-resistant with a wet paper strength agent. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2012-87431 [Overview of the Initiative] [Problems that the invention aims to solve]
[0005] However, conventional base paper for processing had problems such as insufficient tensile strength and gloss.
[0006] This invention has been made in view of these circumstances, and provides a base paper for processing that has excellent tensile strength and gloss. [Means for solving the problem]
[0007] Through diligent research, the inventors discovered that by incorporating a first fibrous cellulose with a fiber diameter of 100 μm or less into the base paper for processing, and by highly adjusting the manufacturing conditions so that the moisture absorption characteristics measured by a specific measurement method fall within a specific numerical range, a base paper for processing with excellent tensile strength and gloss can be obtained, thus completing the present invention.
[0008] The following are examples of various embodiments of the present invention. The embodiments shown below can be combined with each other. [1] A base paper for processing containing fibrous cellulose, wherein the fibrous cellulose includes first fibrous cellulose with a fiber diameter of 100 μm or less, and the ratio M1 / M0 of the mass M0 of the base paper for processing when it is conditioned at 23°C and 50% relative humidity to 1.060 or more, as measured by the following measurement method, to the mass M1 of the base paper for processing after it has been conditioned at 23°C and 90% relative humidity and then moved to 23°C and 50% relative humidity and left to stand for 60 seconds. (Measurement method) • Cut the aforementioned base paper for processing and prepare test base paper for processing. The mass of the test processing base paper after it has been conditioned in an environment of 23°C and 50% relative humidity is defined as M0 (g). The test processing base paper, which has been conditioned at 23°C and 50% relative humidity, is left to stand for 4 hours in an environment of 23°C and 90% relative humidity. Then, it is moved to an environment of 23°C and 50% relative humidity and left to stand for 60 seconds. The mass after this period is defined as M1 (g). A base paper for processing as described in [2][1], wherein the ratio M10 / M0 of the mass M0 of the base paper for processing when conditioned at 23°C and 50% relative humidity, measured by the following measurement method, to the mass M10 after the base paper for processing has been conditioned at 23°C and 90% relative humidity, then moved to 23°C and 50% relative humidity and left to stand for 600 seconds, is 1.040 or more. (Measurement method) • Cut the aforementioned base paper for processing and prepare test base paper for processing. - The mass of the test processing base paper after it has been conditioned in an environment of 23°C and 50% relative humidity shall be M0 (g). - The test processing base paper that has been conditioned in an environment of 23°C and 50% relative humidity shall be left to stand for 4 hours in an environment of 23°C and 90% relative humidity, then moved to an environment of 23°C and 50% relative humidity, and the mass after it has been left to stand for 600 seconds shall be M10 (g). A base paper for processing as described in [3][1] or [2], wherein the tensile strength measured in accordance with JIS P 8113 is 37.00 MPa or higher. A base paper for processing according to any of [4][1] to [3], wherein the fibrous cellulose includes a second fibrous cellulose, and the second fibrous cellulose is different from the first fibrous cellulose. A base paper for processing according to any one of [5][1] to [4], wherein the first fibrous cellulose comprises fibrous cellulose having one or more substituents selected from the group consisting of a phosphorus oxo acid group or substituents derived from a phosphorus oxo acid group, a carboxyl group or substituents derived from a carboxyl group, a sulfur oxo acid group or substituents derived from a sulfur oxo acid group, a xantate group or substituents derived from a xantate group, a phosphonone group or substituents derived from a phosphonone group, a phosphine group or substituents derived from a phosphine group, a sulfone group or substituents derived from a sulfone group, and a carboxyalkyl group. A base paper for processing described in any of [6][1] to [5], which is used as a base paper for paper yarn. A base paper for paper yarn, consisting of the base paper for processing described in any of [7][1] to [6]. A twisted yarn made by processing the paper yarn base described in [8] and [7]. A textile made by processing the twisted yarn described in [9][8]. A pile for carpets made by processing the twisted yarn described in
[10] [8]. A pile for floor covering as described in
[11]
[10] , which is used as the pile portion of an artificial turf installation or floor covering. Fabric made by processing the textiles described in
[12] [9].
[13] A method for producing base paper for processing, comprising an immersion step and a drying step, wherein in the immersion step, a paper substrate containing a second fibrous cellulose is immersed in a dispersion containing a first fibrous cellulose with a fiber diameter of 100 μm or less to obtain wet paper, and in the drying step, the wet paper is dried to obtain base paper for processing. A method for producing the first fibrous cellulose as described in
[14]
[13] , wherein the first fibrous cellulose has a B-type viscosity of more than 7000 mPa·s when measured at 20°C and 60 rpm in a 1% (w / v) aqueous dispersion. A method for producing fibrous cellulose according to
[15]
[13] or
[14] , wherein the first fibrous cellulose comprises a fibrous cellulose having one or more substituents selected from the group consisting of a phosphorus oxoacid group or substituents derived from a phosphorus oxoacid group, a carboxyl group or substituents derived from a carboxyl group, a sulfur oxoacid group or substituents derived from a sulfur oxoacid group, a xantate group or substituents derived from a xantate group, a phosphonone group or substituents derived from a phosphonone group, a phosphine group or substituents derived from a phosphine group, a sulfone group or substituents derived from a sulfone group, and a carboxyalkyl group.
[16] A base paper for processing containing fibrous cellulose, wherein the fibrous cellulose comprises a first fibrous cellulose and a second fibrous cellulose, the first fibrous cellulose having a fiber diameter of 100 μm or less, and the base paper for processing is obtained by immersing a paper substrate containing the second fibrous cellulose in a dispersion containing the first fibrous cellulose to obtain wet paper, and drying the wet paper. [Effects of the Invention]
[0009] The base paper for processing according to the present invention is excellent in tensile strength and gloss, and can produce processed products excellent in strength and gloss. The base paper for paper yarn according to the present invention is excellent in tensile strength and gloss, and can produce paper yarns, twisted yarns, textiles, pile for rugs, and fabrics that are excellent in strength and gloss. The twisted yarn according to the present invention is excellent in strength and gloss, and can produce textiles and pile for rugs that are excellent in strength and gloss. The textile and pile for rugs according to the present invention are excellent in strength and gloss. According to the method for producing a base paper for processing of the present invention, it is possible to produce a processed product that is excellent in tensile strength and gloss, and excellent in strength and gloss. [Brief Description of the Drawings]
[0010] [Figure 1] Figure 1 is a graph showing the relationship between the amount of NaOH added dropwise and the pH for a fibrous cellulose-containing slurry having a phosphorus oxo acid group. [Modes for Carrying Out the Invention]
[0011] Hereinafter, embodiments of the present invention will be described. Various features shown in the embodiments below can be combined with each other. In addition, the invention can be established independently for each feature. Furthermore, among the following embodiments, elements not specified in the claims are optional elements and can be omitted. An arbitrary number (for example, 1 or 2) of "0" may be added to the end of the numerical values disclosed in the following description. For example, one or two "0" may be added after "1.4" to make it "1.40" or "1.400".
[0012] 1 Base paper for processing The base paper for processing according to the present invention is a base paper for processing containing fibrous cellulose, the fibrous cellulose contains first fibrous cellulose having a fiber diameter of 100 μm or less, and the base paper for processing has moisture absorption characteristics measured by a specific measurement method within a specific numerical range.
[0013] 1.1 Features of base paper for processing 1.1.1 Moisture absorption characteristics (mass behavior accompanying humidity change) The base paper for processing according to the present invention has a ratio M1 / M0 of 1.060 or more between the mass M0 of the base paper for processing when it is conditioned at 23°C and 50% relative humidity, and the mass M1 of the base paper after it has been conditioned at 23°C and 90% relative humidity, then moved to 23°C and 50% relative humidity and left to stand for 60 seconds, as measured by the following measurement method. (Measurement method) • Cut the aforementioned base paper for processing and prepare test base paper for processing. The mass of the test processing base paper after it has been conditioned in an environment of 23°C and 50% relative humidity is defined as M0 (g). The test processing base paper, which has been conditioned at 23°C and 50% relative humidity, is left to stand for 4 hours in an environment of 23°C and 90% relative humidity. Then, it is moved to an environment of 23°C and 50% relative humidity and left to stand for 60 seconds. The mass after this period is defined as M1 (g).
[0014] M1 / M0 is 1.060 or greater, and preferably 1.070 or greater. Specifically, M1 / M0 can be, for example, 1.060, 1.062, 1.064, 1.066, 1.068, 1.070, 1.072, 1.074, 1.076, 1.078, 1.080, 1.082, 1.084, 1.086, 1.088, 1.090, 1.092, 1.094, 1.096, 1.098, 1.100, and may also be within the range of any two of the values exemplified here. By keeping M1 / M0 within the above numerical range, a base paper for processing with excellent tensile strength and gloss is obtained.
[0015] The mechanism by which setting M1 / M0 within the above numerical range results in a base paper for processing with excellent tensile strength and gloss is not clear, but it is speculated as follows. First, when the base paper for processing is left standing under high humidity conditions (an environment with 90% relative humidity), the base paper absorbs moisture and its mass increases. The amount of moisture absorbed here is thought to be related to the amount of fibrous cellulose and hydroxyl groups contained in the base paper for processing according to the present invention. Furthermore, the mass after moving the base paper to an environment with 50% relative humidity and leaving it standing for 60 seconds corresponds to the moisture adsorbed onto the base paper and maintained adsorption for 60 seconds. The length of time that the moisture adsorbed onto the base paper remains adsorbed is thought to be related not only to the amount of fibrous cellulose (especially the first fibrous cellulose) and hydroxyl groups in the base paper for processing, but also to the ease with which the adsorbed moisture is released, for example, whether the moisture adsorption sites are mostly on the surface or mostly inside the base paper. Therefore, it is presumed that by controlling the M1 / M0 ratio, which corresponds to the amount of moisture adsorbed and maintained for 60 seconds under specific conditions, within a specific numerical range, the amount of fibrous cellulose (especially primary fibrous cellulose) and hydroxyl groups contained in the base paper for processing, and their distribution, can be indirectly controlled, and by controlling these, base paper for processing with excellent tensile strength and gloss can be obtained. Furthermore, the above-described inference mechanism does not limit the present invention.
[0016] M1 / M0 can be measured using the measurement method described above. The size of the test processing paper is not particularly limited, but it can be 280-300mm x 180-200mm. The base paper for testing and processing can have a length (MD) of 280-300 mm, specifically, for example, 280, 282, 284, 286, 288, 290, 292, 294, 296, 298, and 300 mm, and may also be within the range of any two of the values exemplified here. The base paper for processing can be 180-200 mm in the horizontal direction (CM), specifically, for example, 180, 182, 184, 186, 188, 190, 192, 194, 196, 198, 200 mm, and may also be within the range of any two of the values exemplified here. The thickness of the test processing base paper is not particularly limited, but for example, it may be 1, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, or 100 μm, and may be within the range of any two of the values exemplified here. The base paper for testing and processing can have a mass of 0.900 to 1.000 g. Specifically, the mass of the base paper for testing and processing can be, for example, 0.900, 0.910, 0.920, 0.930, 0.940, 0.950, 0.960, 0.970, 0.980, 0.990, or 1.000 g, and may also be within the range of any two of the values exemplified here.
[0017] The base paper for testing and processing is first conditioned in an environment of 23°C and 50% relative humidity. "Conditioning in an environment of 23°C and 50% relative humidity" means leaving it undisturbed in an environment of 23°C and 50% relative humidity until there is no change in mass (specifically, until the change in mass is 0.001g or less). The specific resting time depends on the humidity control history of the base paper being tested. If the humidity control history of the base paper is unknown, for example, it can be dried at 90°C and then conditioned at 23°C with a relative humidity of 50%. The drying time at 90°C could be, for example, 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, or 20 minutes, and could be within the range of any two of these values. The humidity control time at 23°C with a relative humidity of 50% could be, for example, 0, 2, 4, 6, 8, 10, 12, 14, 16, 17, 18, 19, or 20 hours, and could be within the range of any two of these values. As an example, after drying at 90°C for 12 minutes, the humidity control time at 23°C with a relative humidity of 50% could be 17 hours (or 17 hours or more).
[0018] M1 / M0 can be controlled by adjusting the manufacturing conditions of the base paper for processing. For example, it can be adjusted by the type of fibrous cellulose, the type of base paper, the method of adding the first fibrous cellulose (described later), the concentration and viscosity of the fibrous cellulose aqueous dispersion, and whether or not a squeezing treatment is performed.
[0019] The base paper for processing according to the present invention preferably has a ratio M10 / M0 of 1.040 or higher, more preferably 1.055 or higher, and even more preferably 1.060 or higher, between the mass M0 of the base paper for processing when it is conditioned at 23°C and 90% relative humidity, and the mass M10 after it has been conditioned at 23°C and 50% relative humidity and then moved to 23°C and 50% relative humidity and left to stand for 600 seconds, as measured by the following measurement method. Specifically, M10 / M0 can be, for example, 1.040, 1.042, 1.044, 1.046, 1.048, 1.050, 1.052, 1.054, 1.056, 1.058, 1.060, 1.062, 1.064, 1.066, 1.068, 1.070, 1.072, 1.074, 1.076, 1.078, 1.080, 1.082, 1.084, 1.086, 1.088, 1.090, and may also be within the range of any two of the values exemplified here. By keeping M10 / M0 within the above numerical range, a base paper for processing with superior tensile strength and gloss is obtained.
[0020] The mechanism by which setting M10 / M0 within the above numerical range results in a base paper for processing with excellent tensile strength and gloss is not clear, but it is speculated as follows. First, as described above, when the base paper for processing is left to stand under high humidity conditions (an environment with 90% relative humidity), the base paper absorbs moisture and its mass increases. The amount of moisture absorbed here is thought to be related to the amount of fibrous cellulose and hydroxyl groups contained in the base paper for processing according to the present invention. Furthermore, the mass after moving the base paper to an environment with 50% relative humidity and leaving it to stand for 600 seconds corresponds to the amount of moisture adsorbed onto the base paper and maintained adsorption for 600 seconds. M10 / M0, which corresponds to the amount of moisture adsorbed under specific conditions and maintained for 600 seconds, is thought to be related to the amount of moisture that was adsorbed for a longer period of time, i.e., the amount of moisture adsorbed in locations in the base paper that are relatively difficult to remove (for example, fibrous cellulose and hydroxyl groups present inside the base paper for processing), compared to M1 / M0, which corresponds to the amount of moisture adsorbed under specific conditions and maintained for 60 seconds. Therefore, by controlling the M10 / M0 ratio, which corresponds to the amount of moisture absorbed and maintained for 600 seconds under specific conditions, within a specific numerical range, the amount of fibrous cellulose (especially primary fibrous cellulose) and hydroxyl groups contained in the base paper for processing, and their distribution, can be indirectly controlled. It is presumed that by controlling these, base paper for processing with superior tensile strength and gloss can be obtained. Furthermore, M10 / M0 defines the distribution of moisture adsorption sites from a different perspective than M1 / M0, and it is presumed that by defining M10 / M0, the amount of fibrous cellulose (especially primary fibrous cellulose) and hydroxyl groups contained in the base paper for processing, and their distribution, can be more precisely defined, resulting in base paper for processing with even superior tensile strength and gloss. Furthermore, the above-described inference mechanism does not limit the present invention.
[0021] M10 / M0 can be measured using the above measurement method, and the size of the test processing base paper, humidity control under conditions of 23°C and 50% relative humidity, etc., are as described above.
[0022] M10 / M0 can be controlled by adjusting the manufacturing conditions of the base paper for processing. For example, it can be adjusted by the type of fibrous cellulose, the type of base paper, the method of adding the first fibrous cellulose, the concentration and viscosity of the fibrous cellulose aqueous dispersion, and whether or not a squeezing treatment is performed.
[0023] The base paper for processing according to the present invention preferably has an M10 / M1 ratio of less than 0.985. Specifically, M10 / M1 is, for example, 0.970, 0.971, 0.972, 0.973, 0.974, 0.975, 0.976, 0.977, 0.978, 0.979, 0.980, 0.981, 0.982, 0.983, 0.984, and may also be within the range of any two of the values exemplified here. By keeping M10 / M1 within the above numerical range, a base paper for processing with superior tensile strength and gloss is obtained.
[0024] M10 / M1 can be calculated from M10 and M1 (or M10 / M0 and M1 / M0) obtained by the measurement method described above.
[0025] M10 / M0 can be controlled by adjusting the manufacturing conditions of the base paper for processing. For example, it can be adjusted by the type of fibrous cellulose, the type of base paper, the method of adding fibrous cellulose, the concentration and viscosity of the aqueous dispersion of fibrous cellulose, and whether or not a squeezing treatment is performed.
[0026] 1.1.2 Tensile Strength The base paper for processing according to the present invention preferably has a tensile strength of 37.00 MPa or higher, as measured in accordance with JIS P 8113. Specifically, the tensile strength may be, for example, 37.00, 38.00, 39.00, 40.00, 41.00, 42.00, 43.00, 44.00, 45.00, 46.00, 47.00, 48.00, 49.00, or 50.00 MPa, and may also be within the range of any two of the values exemplified here. Tensile strength can be adjusted by controlling the type of fibrous cellulose, the type of base paper, and the manufacturing conditions of the base paper for processing (method of adding fibrous cellulose, concentration and viscosity of the aqueous dispersion of fibrous cellulose, presence or absence of squeezing treatment, etc.) in order to adjust the hygroscopic properties. The processing base paper according to the present invention can achieve an even higher level of both tensile strength and gloss by adjusting the type of fibrous cellulose, the type of base paper, and the manufacturing conditions of the processing base paper so that the tensile strength is 37.00 MPa or higher. The tensile strength can be measured in accordance with JIS P 8113:2006 and evaluated by the method described in the examples.
[0027] 1.1.3 Basis weight The basis weight of the complete processing paper is specifically, for example, 10.00, 10.50, 11.00, 11.50, 12.00, 12.50, 13.00, 13.50, 14.00, 14.50, 15.00, 15.50, 16.00, 16.50, 17.00, 17.50, 18.00, 18.50, 19.00, 19.50, 20.00, and 22.00 g / m². 2 The basis weight may be within the range of any two of the values exemplified here. The basis weight can be measured after the base paper for processing has been conditioned in an environment of 23°C and 50% relative humidity. The basis weight can be evaluated using the method described in the examples.
[0028] 1.2 Fibrous Cellulose The fibrous cellulose according to the present invention contains first fibrous cellulose with a fiber diameter of 100 μm or less. The fibrous cellulose according to the present invention is thought to become a base paper for processing with excellent tensile strength and gloss by containing first fibrous cellulose in an amount and distribution such that M1 / M0 is within the above numerical range.
[0029] The fibrous cellulose according to the present invention includes a first fibrous cellulose with a fiber diameter of 100 μm or less, and may contain two or more types of fibrous cellulose. The fibrous cellulose may contain the first fibrous cellulose and a second fibrous cellulose different from the first fibrous cellulose. Second fibrous cellulose may differ from first fibrous cellulose in at least one of the following: aspect ratio, fiber diameter, fiber length, manufacturing method, or raw materials. The first fibrous cellulose and the second fibrous cellulose can have different aspect ratios, with the second fibrous cellulose having a larger (average) aspect ratio than the first fibrous cellulose. Furthermore, the first fibrous cellulose and the second fibrous cellulose can have different fiber diameters. The first fibrous cellulose can have a smaller (average) fiber diameter than the second fibrous cellulose. Furthermore, the first fibrous cellulose and the second fibrous cellulose can have different fiber lengths. The first fibrous cellulose can have a shorter (average) fiber length than the second fibrous cellulose. First fibrous cellulose and second fibrous cellulose can be made using different manufacturing methods and raw materials.
[0030] 1.2.1 Primary fibrous cellulose The fiber diameter of the first fibrous cellulose is 100 μm or less, and can be between 2 nm and 100 μm. The fiber diameters of the first fibrous cellulose can be, for example, 2 nm, 5 nm, 10 nm, 20 nm, 50 nm, 100 nm, 200 nm, 500 nm, 1000 nm, 2 μm, 3 μm, 5 μm, 10 μm, 30 μm, 50 μm, or 100 μm, and may be within the range of any two of the values exemplified here. The first fibrous cellulose can be fine fibrous cellulose. When the first fibrous cellulose is fine fibrous cellulose, the fiber diameter can be, for example, 1000 nm or less. The fiber diameter is preferably, for example, 2 nm or more and 1000 nm or less, more preferably 2 nm or more and 100 nm or less, even more preferably 2 nm or more and 50 nm or less, and particularly preferably 2 nm or more and 10 nm or less. The average fiber diameter can be, for example, 2 nm, 5 nm, 10 nm, 20 nm, 50 nm, 100 nm, 200 nm, 500 nm, or 1000 nm, and may be within the range of any two of the values exemplified here. The average fiber diameter of the first fibrous cellulose can be within the above numerical range.
[0031] The fiber diameter of fibrous cellulose can be measured using, for example, a scanning microscope (SEM), a transmission electron microscope (TEM), or an atomic force microscope (AFM). Depending on the fiber width, the fiber diameter of fibrous cellulose can also be measured using a fiber image analyzer (Valmet FS5, manufactured by Valmet Co., Ltd.), a Kayani fiber length analyzer (FS-200, manufactured by Kayani Automation Co., Ltd.), or an optical microscope. For example, the fiber diameter of fibrous cellulose with a fiber diameter exceeding 1000 nm can be measured using a fiber image analyzer, a Kayani fiber length analyzer, or an optical microscope. When using an electron microscope, the measurement is performed as follows: First, an aqueous suspension of fibrous cellulose with a concentration of 0.05% to 0.1% by mass is prepared, and this suspension is cast onto a hydrophilic carbon film-coated grid to prepare a sample for TEM observation. If wide fibers are present, the SEM image of the surface cast on glass may be observed. Next, observation of electron microscope images is performed at a magnification of 1000x, 5000x, 10000x, or 50000x depending on the width of the fibers to be observed. However, the sample, observation conditions, and magnification should be adjusted to satisfy the following conditions (1) and (2).
[0032] Condition (1) A straight line X is drawn at any point in the observed image, and 20 or more fibers intersect with this straight line X. Condition (2) A line Y is drawn perpendicular to the line in the same image, and 20 or more fibers intersect with line Y.
[0033] For observation images that satisfy the above conditions (1) and (2), the width of the fibers intersecting with lines X and Y is visually read. In this way, at least three sets of observation images of surface areas that do not overlap are obtained. Next, for each image, the width of the fibers intersecting with lines X and Y is read. This allows for the reading of at least 20 × 2 × 3 = 120 fiber diameters. The average of the read fiber diameters is then taken as the number-average fiber diameter of the fibrous cellulose.
[0034] The fiber length of the first fibrous cellulose is not particularly limited, but can be, for example, 0.1 μm or more and 30 mm or less, preferably 0.1 μm or more and 1000 μm or less, more preferably 0.1 μm or more and 800 μm or less, and even more preferably 0.1 μm or more and 600 μm or less. The fiber length can be, for example, 0.1 μm, 0.5 μm, 2 μm, 3 μm, 5 μm, 10 μm, 30 μm, 50 μm, 100 μm, 300 μm, 500 μm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 10 mm, 15 mm, 20 mm, 25 mm, or 30 mm, and may be within the range of any two of the values exemplified here. By keeping the fiber length within the above range, the fracture of the crystalline region of fibrous cellulose can be suppressed. The fiber length of fibrous cellulose can be determined, for example, by image analysis using TEM, SEM, AFM, or optical microscope. The fiber length can be the average value for n=12.
[0035] The first fibrous cellulose preferably has a type I crystalline structure. The presence of a type I crystalline structure in the fibrous cellulose can be identified by the diffraction profile obtained from a wide-angle X-ray diffraction photograph using graphite-monochromatized CuKα (λ=1.5418Å). Specifically, it can be identified by the presence of typical peaks at two locations: around 2θ=14° to 17° and around 2θ=22° to 23°. The proportion of type I crystalline structure in the fibrous cellulose is preferably 30% or more, more preferably 40% or more, and even more preferably 50% or more. The degree of crystallinity can be determined by measuring the X-ray diffraction profile and analyzing its pattern using conventional methods (Seagal et al., Textile Research Journal, Vol. 29, p. 786, 1959).
[0036] The aspect ratio (fiber length / fiber diameter) of the first fibrous cellulose is not particularly limited, but is preferably 50 to 10000, and more preferably 100 to 1000. Specifically, the aspect ratios are, for example, 100, 125, 150, 175, 200, 225, 250, 275, 300, 325, 350, 375, 400, 425, 450, 475, 500, 525, 550, 575, 600, 625, 650, 675, 700, 725, 750, 775, 800, 825, 850, 875, 900, 925, 950, 975, and 1000, and may be within the range of any two of the values exemplified here. The average aspect ratio of the first fibrous cellulose can be within the above numerical range. By setting the aspect ratio to be above the lower limit, the strength of the base paper for processing can be further improved. Setting the aspect ratio to be below the upper limit is preferable because it makes handling, such as dilution, easier when handling fibrous cellulose as a dispersion. The aspect ratio can be the average value of n=12.
[0037] When a 1% (w / v) aqueous dispersion of the first fibrous cellulose is prepared, it is preferable that the B-type viscosity of the dispersion, measured at 23°C and 60 rpm, is greater than 7000 mPa·s. The B-type viscosity of a 1% (w / v) aqueous dispersion of the first fibrous cellulose, measured at 23°C and 60 rpm, can be between 7000 and 10000 mPa·s, specifically, for example, 7001, 7050, 7100, 7200, 7300, 7400, 7500, 8000, 8500, 9000, 9500, and 10000 mPa·s, and may also be within the range of any two of the values exemplified here. By ensuring that the viscosity of the aqueous dispersion of the first fibrous cellulose, adjusted under specific conditions, falls within the above numerical range, the moisture absorption characteristics of the base paper for processing can be more appropriately adjusted, resulting in a base paper for processing with superior tensile strength and gloss.
[0038] The first fibrous cellulose may have an ionic functional group. The ionic substituent may include, for example, either an anionic group or a cationic group, or both, and it is particularly preferable that the ionic substituent has an anionic group. Furthermore, the ionic substituent is preferably a group introduced into the fibrous cellulose via an ester bond or an ether bond, and more preferably a group introduced into the fibrous cellulose via an ester bond. In this case, the ester bond is preferably formed by the dehydration condensation of the fibrous cellulose and the compound that will become the ionic substituent. In this specification, an ester group can be a structure formed by the dehydration condensation of various acidic groups (e.g., oxoacids such as organic acids and inorganic acids) with a hydroxyl group.
[0039] Examples of anionic groups as ionic groups include phosphorus oxoacid groups or substituents derived from phosphorus oxoacid groups (sometimes simply referred to as phosphorus oxoacid groups), carboxyl groups or substituents derived from carboxyl groups (sometimes simply referred to as carboxyl groups), sulfur oxoacid groups or substituents derived from sulfur oxoacid groups (sometimes simply referred to as sulfur oxoacid groups), xantate groups or substituents derived from xantate groups (sometimes simply referred to as xantate groups), phosphone groups or substituents derived from phosphone groups, phosphine groups or substituents derived from phosphine groups, sulfone groups or substituents derived from sulfone groups, carboxyalkyl groups, and the like. In particular, the anionic group is preferably at least one selected from the group consisting of phosphorus oxoacid group, substituents derived from phosphorus oxoacid group, carboxyl group, sulfur oxoacid group, substituents derived from sulfur oxoacid group, carboxymethyl group, carboxyethyl group, and sulfone group; more preferably at least one selected from the group consisting of phosphorus oxoacid group, substituents derived from phosphorus oxoacid group, carboxyl group, sulfur oxoacid group, and substituents derived from sulfur oxoacid group; and particularly preferably a phosphorus oxoacid group. By introducing a phosphorus oxoacid group as the anionic group, for example, the dispersibility of fibrous cellulose can be further improved even under alkaline or acidic conditions, making it easier to obtain base paper for processing with increased tensile strength and gloss. Examples of cationic groups as ionic groups include ammonium groups, phosphonium groups, and sulfonium groups. Among these, ammonium groups are preferred as the cationic group. The fibrous cellulose according to one embodiment of the present invention may also exclude those containing methyl groups, hydroxypropyl groups, or hydroxyethyl groups.
[0040] A phosphorus oxoacid group or a substituent derived from a phosphorus oxoacid group is, for example, a substituent represented by the following formula (1). Multiple substituents represented by the following formula (1) may be introduced into each fibrous cellulose. In this case, the multiple substituents represented by the following formula (1) may be the same or different.
[0041] [ka]
[0042] In equation (1), a, b, and n are natural numbers, and m is any number (where a = b × m). Of the n α and α', at least one is O - And the rest are R or OR. Note that all of each α and α' are O - It is acceptable for this to be the case. The n αs may all be the same, or they may all be different. β b+ It is a cation with one or more valencies, composed of organic or inorganic substances.
[0043] R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an unsaturated cyclic hydrocarbon group, an aromatic group, or a derivative thereof. In formula (1), n is preferably 1.
[0044] Examples of saturated linear hydrocarbon groups include, but are not limited to, methyl, ethyl, n-propyl, or n-butyl groups. Examples of saturated branched hydrocarbon groups include, but are not limited to, i-propyl or t-butyl groups. Examples of saturated cyclic hydrocarbon groups include, but are not limited to, cyclopentyl or cyclohexyl groups. Examples of unsaturated linear hydrocarbon groups include, but are not limited to, vinyl or allyl groups. Examples of unsaturated branched hydrocarbon groups include, but are not limited to, i-propenyl or 3-butenyl groups. Examples of unsaturated cyclic hydrocarbon groups include, but are not limited to, cyclopentenyl or cyclohexenyl groups. Examples of aromatic groups include, but are not limited to, phenyl or naphthyl groups.
[0045] Furthermore, the derivative group in R is a functional group obtained by adding or substituting at least one functional group selected from carboxyl groups, carboxylate groups (-COO-), hydroxyl groups, amino groups, and ammonium groups to the main chain or side chain of the various hydrocarbon groups mentioned above, but is not particularly limited. Also, the number of carbon atoms constituting the main chain of R is not particularly limited, but is preferably 20 or less, and more preferably 10 or less. By setting the number of carbon atoms constituting the main chain of R within the above range, the molecular weight of the phosphorus oxoacid group can be set within an appropriate range, which facilitates penetration into the fiber raw material and can increase the yield of fibrous cellulose. Note that if there are multiple Rs in formula (1) or if multiple substituents represented by formula (1) are introduced into fibrous cellulose, the multiple Rs may be the same or different.
[0046] β b+is a monovalent or higher cation composed of an organic substance or an inorganic substance. Examples of the monovalent or higher cation composed of an organic substance include organic onium ions. Examples of the organic onium ions include organic ammonium ions and organic onium ions. Examples of the organic ammonium ions include aliphatic ammonium ions and aromatic ammonium ions, and examples of the organic onium ions include aliphatic phosphonium ions and aromatic phosphonium ions. Examples of the monovalent or higher cation composed of an inorganic substance include ions of alkali metals such as sodium, potassium, or lithium, ions of divalent metals such as calcium or magnesium, hydrogen ions, ammonium ions, and the like. In addition, in formula (1), β b+ are present in plural numbers, or when a plurality of types of substituents represented by formula (1) are introduced into fibrous cellulose, the plurality of β b+ may be the same or different from each other. As the monovalent or higher cation composed of an organic substance or an inorganic substance, β b+ sodium or potassium ions, which hardly cause yellowing when the fiber raw material containing the same is heated and are industrially easy to use, are preferable, but there is no particular limitation.
[0047] More specific examples of the phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group include a phosphoric acid group (-PO3H2), a salt of the phosphoric acid group, a phosphorous acid group (phosphonic acid group) (-PO2H2), and a salt of the phosphorous acid group (phosphonic acid group). In addition, the phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group may be a group obtained by condensing a phosphoric acid group (for example, a pyrophosphoric acid group), a group obtained by condensing a phosphonic acid (for example, a polyphosphonic acid group), a phosphoric acid ester group (for example, a monomethyl phosphate group, a polyoxyethylene alkyl phosphate group), an alkylphosphonic acid group (for example, a methylphosphonic acid group), or the like.
[0048] The presence of each ionic functional group in the fibrous cellulose can be confirmed by measuring an infrared absorption spectrum using FT-IR, although it depends on the amount of each ionic functional group. For example, the presence or absence of a phosphoric acid group is determined at 1230 cm -1This can be confirmed based on the absorption of the phosphate group based on P=O in the vicinity.
[0049] The amount of ionic substituent introduced per gram of first fibrous cellulose can be 0.10 to 3.65 mmol / g or less, and more preferably 0.10 to 1.50 mmol or 0.10 to 0.9 mmol / g. The amount of ionic substituent per gram of fibrous cellulose can be, for example, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.80, 2.00, 2.20, 2.40, 2.60, 2.80, 3.00, 3.20, 3.40, 3.60, or 3.65 mmol / g, and may be within the range of any two of the values exemplified here. Here, the denominator in mmol / g is the counterion of the ionic substituent being a hydrogen ion (H + This shows the mass of fibrous cellulose when ).
[0050] A fibrous cellulose according to one embodiment of the present invention has phosphorus oxoacid groups. The first fibrous cellulose can have an amount of phosphorus oxoacid groups introduced per gram of fibrous cellulose of 0.10 to 3.65 mmol / g or less, and more preferably 0.10 to 1.50 mmol or 0.10 to 0.9 mmol / g. The amount of phosphorus oxoacid groups per gram of fibrous cellulose is, for example, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, 1.00, 1.10, 1.20, 1.30, 1.40, 1.50, 1.60, 1.80, 2.00, 2.20, 2.40, 2.60, 2.80, 3.00, 3.20, 3.40, 3.60, and 3.65 mmol / g, and may also be within the range of any two of the values exemplified here.
[0051] By setting the content of ionic functional groups such as phosphorus oxoacid groups above the above lower limit, the micronization of the fiber raw material can be facilitated, and the stability of fibrous cellulose can be improved. Furthermore, according to one embodiment of the present invention, by setting the content of ionic functional groups such as phosphorus oxoacid groups within the above numerical range, particularly below the upper limit, the increase in hydrophilicity can be suppressed by keeping the amount of ionic functional groups below a certain level, thereby reducing water absorption. In addition, for example, by removing some of the substituents such as phosphoric acid groups and replacing them with hydroxyl groups, the water resistance and strength of the resulting base paper for processing can be further improved.
[0052] The amount of ionic substituent introduced into the first fibrous cellulose can be measured, for example, by neutralization titration after the cellulose fibers have been subjected to micronization treatment. In the neutralization titration method, the amount introduced is determined by measuring the change in pH while adding an alkali such as an aqueous sodium hydroxide solution to the slurry containing the obtained fibrous cellulose.
[0053] As an example, let's explain how to determine the amount of phosphorus oxoacid groups. Figure 1 is a graph showing the relationship between the amount of NaOH added to a slurry containing fibrous cellulose with phosphorus oxoacid groups and the pH. The amount of phosphorus oxoacid groups introduced into the fibrous cellulose can be measured, for example, as follows. First, ion-exchanged water is added to the target cellulose fibers to prepare a slurry with a solid content of 0.2% by mass. This slurry is then processed four times at a pressure of 200 MPa using a wet atomizing device (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a fibrous cellulose dispersion (slurry) containing fibrous cellulose. Finally, the fibrous cellulose dispersion is treated with a strongly acidic ion-exchange resin. Next, the pH change is observed while adding an aqueous sodium hydroxide solution, and a titration curve like the one shown in the upper part of Figure 1 is obtained. In the titration curve shown in the upper part of Figure 1, the measured pH is plotted against the amount of alkali added, and in the titration curve shown in the lower part of Figure 1, the increment (derivative value) (1 / mmol) of pH with respect to the amount of alkali added is plotted. In this neutralization titration, two points are observed in the curve plotting the measured pH against the amount of alkali added where the increment (derivative value of pH with respect to the amount of alkali added) is maximum. Of these, the first maximum increment obtained after starting to add alkali is called the first endpoint, and the next maximum increment obtained is called the second endpoint. The amount of alkali required from the start of the titration to the first endpoint is equal to the amount of the first dissociated acid from the fibrous cellulose contained in the slurry used for titration. The amount of alkali required from the first endpoint to the second endpoint is equal to the amount of the second dissociated acid from the fibrous cellulose contained in the slurry used for titration. The amount of alkali required from the start of the titration to the second endpoint is equal to the total amount of dissociated acid from the fibrous cellulose contained in the slurry used for titration. The value obtained by dividing the amount of alkali required from the start of the titration to the first endpoint by the solid content (g) of the slurry being titrated is the amount of phosphorus oxoacid groups introduced (mmol / g). Note that when simply referred to as the amount of phosphorus oxoacid groups introduced (or amount of phosphorus oxoacid groups), it refers to the amount of the first dissociated acid. In Figure 1, the region from the start of titration to the first endpoint is called the first region, and the region from the first endpoint to the second endpoint is called the second region. For example, if the phosphorus oxoacid group is a phosphate group and this phosphate group undergoes condensation, the amount of weakly acidic group in the phosphorus oxoacid group (also referred to as the amount of the second dissociated acid in this specification) appears to decrease, and the amount of alkali required in the second region becomes less than the amount of alkali required in the first region. On the other hand, the amount of strongly acidic group in the phosphorus oxoacid group (also referred to as the amount of the first dissociated acid in this specification) is equal to the amount of phosphorus atoms, regardless of whether condensation occurs or not. Also, if the phosphorus oxoacid group is a phosphite group, there is no weakly acidic group in the phosphorus oxoacid group, so the amount of alkali required in the second region becomes less, or in some cases, the amount of alkali required in the second region becomes zero. In this case, there is only one point on the titration curve where the pH increment is maximum.
[0054] The amount of phosphorus oxoacid groups introduced (mmol / g) mentioned above represents the amount of phosphorus oxoacid groups present in acid-type fibrous cellulose, since the denominator represents the mass of acid-type fibrous cellulose (hereinafter referred to as phosphorus oxoacid group amount (acid-type)). On the other hand, if the counterion of the phosphorus oxoacid group is substituted with an arbitrary cation C such that it has a charge equivalent, the amount of phosphorus oxoacid groups present in fibrous cellulose with cation C as the counterion can be determined by converting the denominator to the mass of fibrous cellulose when cation C is the counterion (hereinafter referred to as phosphorus oxoacid group amount (C-type)). That is, it is calculated using the following formula. Phosphorus oxoacid group amount (C type) = Phosphorus oxoacid group amount (acid type) / {1 + (W - 1) × P / 1000} P[mmol / g]: Total amount of anions derived from the phosphorus oxoacid group in fibrous cellulose (total amount of dissociated acids from the phosphorus oxoacid group) W: Formula weight per unit charge of the cation C (e.g., Na is 23, Al is 9)
[0055] In measuring the amount of ionic substituents by titration, if the amount of sodium hydroxide aqueous solution added is too large or the titration interval is too short, accurate values may not be obtained, resulting in a lower-than-actual amount of ionic substituents. Appropriate titration volumes and intervals include, for example, titrating 10 to 50 μL of 0.1 N sodium hydroxide aqueous solution every 5 to 30 seconds.
[0056] The amount (content) of anionic functional groups such as phosphate groups introduced into fibrous cellulose can be controlled by adjusting the manufacturing process and conditions for the fibrous cellulose manufacturing method, particularly by adjusting the presence and conditions of the ionic substituent introduction step, washing step, alkali treatment step (neutralization treatment step), defibration treatment step, and substituent removal step.
[0057] 1.2.2 Method for producing first fibrous cellulose The method for producing the first fibrous cellulose according to the present invention is not particularly limited. The method for producing the first fibrous cellulose according to one embodiment of the present invention may include an ionic substituent introduction step, a washing step, an alkali treatment step (neutralization treatment step), and a defibration treatment step. Furthermore, the method for producing the first fibrous cellulose according to one embodiment of the present invention may include a substituent removal step, a washing step after substituent removal, and a dispersion step after substituent removal.
[0058] The raw material for obtaining the first fibrous cellulose is not particularly limited, but pulp is preferred because it is readily available and inexpensive. Examples of pulp include wood pulp, non-wood pulp, and deinked pulp. Examples of wood pulp include hardwood kraft pulp (LBKP), softwood kraft pulp (NBKP), sulfite pulp (SP), dissolved pulp (DP), soda pulp (AP), unbleached kraft pulp (UKP), oxygen-bleached kraft pulp (OKP), and other chemical pulps. Other examples include semi-chemical pulp (SCP), chemiground wood pulp (CGP), and mechanical pulp (GP), such as crushed wood pulp (TMP, BCTMP), but are not particularly limited. Examples of non-wood pulps include cotton pulps such as cotton linters and cotton lint, non-wood pulps such as hemp, straw, and bagasse, and cellulose, chitin, and chitosan isolated from sea squirts and seaweed, but are not particularly limited. Examples of deinked pulps include deinked pulps made from recycled paper, but are not particularly limited. One type of pulp may be used alone, or two or more types may be mixed. Among the above pulps, wood pulp containing cellulose and deinked pulp are preferred in terms of availability. Among wood pulps, chemical pulp is preferred because it has a high cellulose ratio, resulting in a high yield of fibrous cellulose during fiber refinement (defibration), and because the decomposition of cellulose in the pulp is small, allowing for the production of long-fiber fibrous cellulose with a large aspect ratio. Among these, kraft pulp and sulfite pulp are the most preferred selections. Processing base paper containing long-fiber fibrous cellulose with a large aspect ratio tends to yield high tensile strength.
[0059] [Ionic substituent introduction process] Examples of ionic substituent introduction steps include phosphorus oxoacid group introduction steps, carboxyl group introduction steps, sulfur oxoacid group introduction steps, xantate group introduction steps, phosphone group or phosphine group introduction steps, sulfone group introduction steps, and cationic group introduction steps. Each introduction step can employ known methods, such as those described in Japanese Patent Application Publication No. 2024-92412.
[0060] The amount of each ionic substituent introduced into the fiber raw material can be adjusted so that the amount of ionic substituent introduced falls within the numerical range described above.
[0061] <Washing process> In the process of obtaining cellulose fibers having ionic substituents, a washing step may be performed on the ionic substituent-introduced fibers as needed. The washing step is performed, for example, by washing the ionic substituent-introduced fibers with water or an organic solvent. Furthermore, the washing step may be performed after each of the steps described later, and the number of washing steps performed in each washing step is not particularly limited.
[0062] <Alkali treatment process (neutralization treatment process)> In the process of obtaining cellulose fibers having ionic substituents, an alkali treatment step may be provided between the ionic substituent introduction step and the micronization treatment step. The alkali treatment method is not particularly limited, but one example is immersing the ionic substituent-introduced fibers in an alkaline solution.
[0063] The alkali compound contained in the alkaline solution is not particularly limited and may be an inorganic alkali compound or an organic alkali compound. In this embodiment, it is preferable to use sodium hydroxide or potassium hydroxide as the alkali compound due to its high versatility. The solvent contained in the alkaline solution may be either water or an organic solvent. In particular, the solvent contained in the alkaline solution is preferably water or a polar solvent including a polar organic solvent such as alcohol, and more preferably an aqueous solvent containing at least water. As the alkaline solution, for example, an aqueous solution of sodium hydroxide or an aqueous solution of potassium hydroxide is preferred due to its high versatility.
[0064] The temperature of the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably, for example, 5°C to 80°C, and more preferably 10°C to 60°C. The immersion time of the ionic substituent-introduced fiber in the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably, for example, 5 minutes to 30 minutes, and more preferably 10 minutes to 20 minutes. The amount of alkaline solution used in the alkaline treatment is not particularly limited, but is preferably, for example, 100% by mass to 100,000% by mass, and more preferably 1,000% by mass to 10,000% by mass, relative to the absolute dry mass of the ionic substituent-introduced fiber.
[0065] To reduce the amount of alkaline solution used in the alkaline treatment process, the ionic substituent-introduced fibers may be washed with water or an organic solvent after the ionic substituent introduction process and before the alkaline treatment process. After the alkaline treatment process and before the micronization process, it is preferable to wash the alkaline-treated ionic substituent-introduced fibers with water or an organic solvent to improve handling.
[0066] <Acid treatment process> In the process of obtaining cellulose fibers having ionic substituents, an acid treatment step may be included between the ionic substituent introduction step and the micronization treatment step. For example, the ionic substituent introduction step, acid treatment, alkali treatment, and micronization treatment may be performed in this order. The concentration of the acidic solution used is not particularly limited, but is preferably 10% by mass or less, and more preferably 5% by mass or less. The pH of the acidic solution used is not particularly limited, but is preferably 0 to 4, and more preferably 1 to 3. Examples of acids that can be included in the acidic solution include inorganic acids, sulfonic acids, carboxylic acids, etc. Examples of inorganic acids include sulfuric acid, nitric acid, hydrochloric acid, hydrobromic acid, hydroiodic acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, phosphoric acid, and boric acid. Examples of sulfonic acids include methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid. Examples of carboxylic acids include formic acid, acetic acid, citric acid, gluconic acid, lactic acid, oxalic acid, and tartaric acid. Among these, hydrochloric acid or sulfuric acid is particularly preferred.
[0067] <Fibroid Release Process> By defibrating fiber raw materials or ionic group-introduced fibers in a defibration process, fibrous cellulose, particularly fine fibrous cellulose, can be obtained. Defibration is also called micronization. In the defibration process, for example, a defibration processing device can be used. The defibration processing device is not particularly limited, but for example, a high-speed defibrator, grinder (stone mill type grinder), high-pressure homogenizer or ultra-high-pressure homogenizer, high-pressure impact grinder, ball mill, bead mill, disc type refiner, conical refiner, twin-screw kneader, vibrating mill, homomixer under high-speed rotation, ultrasonic disperser, or beater can be used. Among the above defibration processing devices, it is more preferable to use a high-speed defibrator, high-pressure homogenizer, or ultra-high-pressure homogenizer, which have less influence from the grinding media and less risk of contamination.
[0068] In the defibration process, it is preferable to dilute, for example, the fiber raw material or ionic group-introduced fiber with a dispersion medium to form a slurry. As the dispersion medium, one or more types selected from water and organic solvents such as polar organic solvents can be used. The polar organic solvent is not particularly limited, but preferred examples include alcohols, polyhydric alcohols, ketones, ethers, esters, and aprotic polar solvents. Examples of alcohols include methanol, ethanol, isopropanol, n-butanol, and isobutyl alcohol. Examples of polyhydric alcohols include ethylene glycol, propylene glycol, and glycerin. Examples of ketones include acetone and methyl ethyl ketone (MEK). Examples of ethers include diethyl ether, tetrahydrofuran, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono-n-butyl ether, and propylene glycol monomethyl ether. Examples of esters include ethyl acetate and butyl acetate. Examples of aprotic polar solvents include dimethyl sulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), and N-methyl-2-pyrrolidinone (NMP).
[0069] The solid content concentration of fibrous cellulose during the defibration process can be set as appropriate. Furthermore, the slurry obtained by dispersing ionic group-introduced fibers in a dispersion medium may contain solid components other than ionic group-introduced fibers, such as hydrogen-bonding urea.
[0070] 1.2.3 Secondary fibrous cellulose The base paper for processing according to the present invention may contain a second fibrous cellulose. Secondary fibrous cellulose can be obtained by pulping plant fiber-containing materials using publicly known and publicly available methods. Tree species that can be used as pulp include conifers such as Japanese red pine, Japanese black pine, Sakhalin fir, Yezo spruce, red pine, Japanese larch, fir, hemlock, Japanese cedar, Japanese cypress, Japanese larch, fir, spruce, Japanese cypress, Douglas fir, hemlock, white fir, spruce, balsam fir, cedar, pine, Merkus fir, and radiata pine, as well as broad-leaved trees such as beech, birch, alder, oak, Machilus, Castanopsis, white birch, poplar, ash, willow, eucalyptus, mangrove, and lauan. In addition, hemp, mitsumata, bamboo, and straw can also be pulped and used. Examples of secondary fibrous cellulose include wood-derived pulps such as chemical pulp obtained by pulping coniferous and hardwoods using methods such as the kraft process, sulfite process, soda process, and polysulfide process; mechanical pulp obtained by mechanical force using refiners and grinders; semi-chemical pulp obtained by mechanical force after chemical pretreatment; and recycled paper pulp. Each of these can be used in an unbleached (before bleaching) or bleached (after bleaching) state. Examples of non-wood pulps include fibers obtained by pulping cotton, Manila hemp, flax, straw, bamboo, pagus, and kenaf in the same way as wood pulp. Among these, it is preferable to include bleached hardwood pulp, bleached softwood pulp, and hemp pulp. Hemp includes various types such as taima (cannabis), choma (ramie), bouma (Japanese ramie), kouma (jude), ama (flax), kenaf, Manila hemp, and sisal hemp, but Manila hemp is particularly desirable due to its large aspect ratio.
[0071] The fiber diameter of the secondary fibrous cellulose can be greater than 1 μm. Specifically, the average fiber diameter of the secondary fibrous cellulose can be, for example, 2, 3, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 200, 300, 400, 500, 600, 700, 800, 900, and 1000 μm, and may also be within the range of any two of the values exemplified here. The fiber diameter can be the average fiber diameter of n=12.
[0072] The fiber length of the secondary fibrous cellulose can be, for example, 100 μm or more and 100 mm or less. Specifically, the fiber lengths of the secondary fibrous cellulose can be, for example, 100 μm, 500 μm, 1 mm, 5 mm, 10 mm, 15 mm, 20 mm, 25 mm, 30 mm, 35 mm, 40 mm, 45 mm, 50 mm, 55 mm, 60 mm, 65 mm, 70 mm, 75 mm, 80 mm, 85 mm, 90 mm, 95 mm, and 100 mm, and may be within the range of any two of the values exemplified here. By setting the fiber length within the above range, the tensile strength of the base paper for processing can be further improved. The fiber length can be the average value of n=12.
[0073] The aspect ratio (fiber length / fiber diameter) of the second fibrous cellulose is not particularly limited, but is preferably 50 to 10000, and more preferably 150 to 1000. Specifically, the aspect ratios are, for example, 150, 175, 200, 225, 250, 275, 300, 325, 350, 375, 400, 425, 450, 475, 500, 525, 550, 575, 600, 625, 650, 675, 700, 725, 750, 775, 800, 825, 850, 875, 900, 925, 950, 975, and 1000, and may be within the range of any two of the values exemplified here. By setting the aspect ratio to be above the lower limit value above, the strength of the base paper for processing can be further improved. Setting the aspect ratio below the above upper limit is preferable because it facilitates handling, such as dilution, when dealing with fibrous cellulose as a dispersion. The aspect ratio can be the average value of n=12.
[0074] The methods for measuring and calculating fiber diameter, fiber length, and aspect ratio are as described above in the explanation of the first fibrous cellulose.
[0075] 1.2.4 Blending ratio of fibrous cellulose The base paper for processing according to the present invention may contain 70 to 100% by mass of fibrous cellulose (including first fibrous cellulose and second fibrous cellulose) per 100% by mass of the base paper for processing. Specifically, the content of fibrous cellulose per 100% by mass of the base paper for processing may be, for example, 70, 75, 80, 85, 90, 95, or 100, and may be within the range of any two of the values exemplified herein. The base paper for processing according to the present invention may contain 0.01 to 20% by mass of first fibrous cellulose relative to 100% by mass of fibrous cellulose contained in the base paper for processing. Specifically, the content of first fibrous cellulose relative to 100% by mass of fibrous cellulose is, for example, 0.01, 0.02, 0.03, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 1.0, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, and 20% by mass, and may be within the range of any two of the values exemplified here. By keeping the content of primary fibrous cellulose within the above numerical range, the moisture absorption characteristics can be adjusted more appropriately, making it easier to obtain a base paper for processing that has superior tensile strength and gloss. The base paper for processing according to the present invention may contain 80 to 99.9% by mass of secondary fibrous cellulose relative to 100% by mass of fibrous cellulose contained in the base paper for processing. Specifically, the content of secondary fibrous cellulose relative to 100% by mass of fibrous cellulose is, for example, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 99.5, 99.9% by mass, and may be within the range of any two of the values exemplified here. The base paper for processing according to the present invention may contain components other than fibrous cellulose based on 100% by mass of the base paper for processing. Specifically, the content of components other than fibrous cellulose based on 100% by mass of the base paper for processing may be, for example, 0, 5, 10, 15, 20, 25, or 30% by mass, and may be within the range of any two of the values exemplified herein.
[0076] 1.3 Other ingredients The base paper for processing according to the present invention may also contain, depending on the purpose and as needed, water-resistant agents, pH adjusters, defoaming agents, thickeners, pigments, starch, etc.
[0077] The base paper for processing according to one embodiment of the present invention may also contain starch. Starch is a polymer of D-glucose, preferably a mixture of amylose and amylopectin. In this embodiment, starch also includes high-molecular-weight compounds derived from starch. Examples of such high-molecular-weight compounds include those obtained by modifying, altering, or processing starch. The starch content in the base paper for processing may be less than 67 parts by mass, when the content of primary fibrous cellulose in the base paper for processing is taken as 1 part by mass. Specifically, for example, it may be 0, 1, 2, 3, 4, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, or 66 parts by mass, and may also be within the range of any two of the values exemplified here. The base paper for processing does not need to contain starch.
[0078] The base paper for processing according to one embodiment of the present invention may also contain pigments. Examples of commonly used pigments include calcium carbonate, kaolin, clay, calcined kaolin, amorphous silica, zinc oxide, aluminum oxide, satin white, aluminum silicate, magnesium silicate, magnesium carbonate, titanium dioxide, and plastic pigments. Examples of calcium carbonate include light calcium carbonate and heavy calcium carbonate. The pigment content in the base paper for processing can be less than 500 parts by mass, with the content of the first fibrous cellulose in the base paper for processing being 1 part by mass. Specifically, for example, this could be 0, 5, 10, 20, 30, 40, 50, 100, 150, 200, 250, 300, 350, 400, 450, or 499 parts by mass, and may also be within the range of any two of the values exemplified here.
[0079] The base paper for processing according to one embodiment of the present invention may also contain a paper strength enhancer and / or a wet paper strength enhancer. Examples of paper strength enhancers include urea-formaldehyde resin, melamine-formaldehyde resin, polyamide-polyamine-epichlorohydrin resin, polyvinylamine resin, cationized starch, cationic polyacrylamide resin, amphoteric polyacrylamide resin, glyoxal, gum, mannogalactan polyethyleneimine, polyacrylamide resin, polyvinyl alcohol, carboxymethylcellulose, guar gum, urea resin, and the like. The amount of paper strength enhancers and wet paper strength enhancers contained in the base paper for processing may be less than 10 parts by mass and less than 0.4 parts by mass per 100 parts by mass of fibrous cellulose contained in the base paper for processing. Specifically, for example, these may be 0.0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, and may also be within the range of any two of the values exemplified here. The base paper for processing according to one embodiment of the present invention exhibits excellent tensile strength and gloss even when the amount of the above-mentioned components is reduced or omitted.
[0080] 1.4 Application The base paper for processing according to the present invention can be used for a variety of purposes, and processed products with excellent tensile strength and gloss can be obtained. For example, the base paper for processing according to the present invention can be used as base paper for paper yarn. By cutting the base paper for paper yarn into long, narrow strips and twisting them, twisted yarn (paper yarn) can be obtained. The base paper for processing and the twisted yarn made by processing the base paper for paper yarn according to the present invention have excellent strength and gloss. The twisted yarn can also be dyed in the same way as ordinary yarn. Furthermore, the twisted yarn according to the present invention can be used in the manufacture of woven fabrics (textiles), knitted fabrics, piles for floor coverings, etc., and can be used in the manufacture of cloth, artificial turf coverings, floor coverings, etc. The cloth according to the present invention, for example, textiles and fabrics made by processing textiles have excellent strength and gloss, and can be used for wallpaper, canvases for oil paintings, tatami mats, rush mats, sportswear for karate, yukata sashes, shirts, work clothes, handkerchiefs, towels, curtains, etc. The pile material for floor coverings according to the present invention has excellent strength and gloss, and can be used as the pile portion of artificial turf installations, carpets, rugs, mats, and other floor coverings.
[0081] As another example, by bending or performing other processes on the processing base paper according to the present invention, or on a sheet laminated on the processing base paper, it is possible to manufacture tubes, containers, lids for containers, and various other three-dimensional paper products. Processed products using the processing base paper according to the present invention have excellent strength and gloss.
[0082] 2. Method for manufacturing base paper for processing The method for producing base paper for processing according to the present invention includes an immersion step and a drying step. In the immersion step, a paper substrate (base paper) containing second fibrous cellulose is immersed in a dispersion containing first fibrous cellulose with a fiber diameter of 100 μm or less to obtain wet paper. In the drying step, the wet paper is dried to obtain base paper for processing.
[0083] 2.1 Dispersion liquid preparation process The method for producing base paper for processing according to the present invention may include a dispersion preparation step. In the dispersion preparation step, a dispersion containing first fibrous cellulose is prepared. The characteristics and production method of first fibrous cellulose are as described above. The first fibrous cellulose may contain one or more substituents selected from the group consisting of a phosphorus oxoacid group or substituents derived from a phosphorus oxoacid group, a carboxyl group or substituents derived from a carboxyl group, a sulfur oxoacid group or substituents derived from a sulfur oxoacid group, a xantate group or substituents derived from a xantate group, and preferably has substituents derived from a phosphorus oxoacid group or phosphorus oxoacid group, a phosphone group or substituents derived from a phosphone group, a phosphine group or substituents derived from a phosphine group, a sulfone group or substituents derived from a sulfone group, and a carboxyalkyl group.
[0084] The first fibrous cellulose preferably has a B-type viscosity of over 7000 mPa·s in a 1% (w / v) aqueous dispersion, measured at 20°C and 60 rpm. The B-type viscosity of a 1% (w / v) aqueous dispersion of the first fibrous cellulose, measured at 20°C and 60 rpm, can be between 7000 and 10000 mPa·s, specifically, for example, 7001, 7050, 7100, 7200, 7300, 7400, 7500, 8000, 8500, 9000, 9500, and 10000 mPa·s, and may also be within the range of any two of the values exemplified here. In the dispersion preparation step, if necessary, for example, the solid content concentration of the dispersion containing the first fibrous cellulose obtained by the above-described method for producing the first fibrous cellulose can be adjusted to obtain a dispersion for the immersion step. The solid content concentration of the dispersion can be 0.05 to 5% by mass, specifically, for example, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, and 5.0% by mass, and may also be within the range of any two of the values exemplified here. By using a dispersion with the above viscosity characteristics and / or concentration, i.e., a dispersion with a relatively high concentration which may make coating or papermaking difficult, and adding the first fibrous cellulose by immersion, the dispersion will be appropriately impregnated into the paper substrate (base paper) containing the second fibrous cellulose, resulting in a base paper for processing in which the first fibrous cellulose is appropriately distributed within the base paper of the second fibrous cellulose. This is thought to adjust the humidity characteristics (M1 / M0 or M10 / M0) and make it easier to obtain a base paper for processing with superior strength and gloss.
[0085] 2.2 Soaking process In the immersion process, a paper substrate (base paper) containing a second fibrous cellulose is immersed in a dispersion containing a first fibrous cellulose with a fiber diameter of 100 μm or less to obtain wet paper. As the paper substrate, a base paper containing secondary fibrous cellulose can be used. The secondary fibrous cellulose is as described above. The base paper can be made from paper obtained by forming the second fibrous cellulose described above. The base paper may be mainly composed of secondary fibrous cellulose, and may contain other components as needed. The base paper may contain 50 to 100 parts by mass of secondary fibrous cellulose per 100 parts by mass of base paper. Specifically, the content of secondary fibrous cellulose in the base paper may be, for example, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100 parts by mass, and may be within the range of any two of the values exemplified here. The basis weight of the base paper is 10.00, 10.50, 11.00, 11.50, 12.00, 12.50, 13.00, 13.50, 14.00, 14.50, 15.00, 15.50, 16.00, 16.50, 17.00, 17.50, 18.00, 18.50, 19.00, 19.50, and 20.00 g / m². 2 Furthermore, the value may be within the range of any two of the values exemplified here. The basis weight may be measured after the base paper has been conditioned in an environment of 23°C and 50% relative humidity.
[0086] The base paper can be 280-300 mm in the vertical direction (MD), specifically, for example, 280, 282, 284, 286, 288, 290, 292, 294, 296, 298, 300 mm, and may also be within the range of any two of the values exemplified here. The base paper can be 180-200 mm in the horizontal direction (CM), specifically, for example, 180, 182, 184, 186, 188, 190, 192, 194, 196, 198, 200 mm, and may also be within the range of any two of the values exemplified here.
[0087] The immersion process can be carried out by filling a container with a dispersion containing primary fibrous cellulose and immersing the base paper for a certain period of time. The immersion time is not particularly limited, but specifically, for example, it could be 10 seconds, 20 seconds, 30 seconds, 40 seconds, 50 seconds, 60 seconds, 1 minute, 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, or 10 minutes, and may be within the range of any two of the values exemplified here.
[0088] The method for manufacturing base paper for processing according to the present invention may also include a squeezing step after the immersion step. In the squeezing step, at least a portion of the dispersion can be removed by sandwiching the wet paper removed from the dispersion between cardboard or the like and squeezing it. The manufacturing method for base paper for processing according to the present invention involves a coating amount per unit area of wet paper after the immersion step and, if necessary, a squeezing step, which is 0.01 to 5.00 g / m². 2 Specifically, for example, 0.01, 0.02, 0.03, 0.04, 0.05, 0.10, 0.20, 0.30, 0.40, 0.50, 1.00, 1.50, 2.00, 2.05, 3.00, 3.50, 4.00, 4.50, 5.00 g / m³ 2 And it may be within the range of any two of the numbers exemplified here.
[0089] 2.3 Drying process In the drying process, the wet paper is dried to obtain base paper for processing. The drying temperature can be 40 to 100°C, specifically, for example, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, and 100°C, and may also be within the range of any two of the values exemplified here. The drying time may be, for example, 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, or 20 minutes, and may be within the range of any two of the values exemplified here.
[0090] A processing base paper according to one embodiment of the present invention is a processing base paper containing fibrous cellulose, wherein the fibrous cellulose comprises first fibrous cellulose and second fibrous cellulose, and the processing base paper is obtained by immersing a paper substrate containing second fibrous cellulose in a dispersion containing first fibrous cellulose to obtain wet paper, and then drying the wet paper. In one embodiment of the present invention, the base paper for processing, by adding first fibrous cellulose by immersion, is expected to result in a base paper for processing in which the dispersion liquid is appropriately impregnated into the paper substrate (base paper) containing second fibrous cellulose, and the first fibrous cellulose is appropriately distributed within the substrate of second fibrous cellulose, making it easier to obtain a base paper for processing with excellent strength and gloss.
[0091] 3. Paper for paper yarn, twisted yarn, cloth, textiles, fabrics, and pile for rugs. The base paper for paper yarn according to one embodiment of the present invention may be made of the above-mentioned base paper for processing. Furthermore, twisted yarn (paper yarn) can be obtained by slitting the paper base for paper yarn according to the present invention into long, narrow strips and twisting them. A twisted yarn according to one embodiment of the present invention may be made by processing the above-mentioned base paper for paper yarn. A method for manufacturing twisted yarn according to one embodiment of the present invention may include a slitting step of slitting the paper yarn base according to the present invention into, for example, widths of 0.5 to 8.0 mm to obtain paper tape, and a twisting step of twisting the paper tape to obtain twisted yarn. The width of the strips can be, for example, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, or 15.0 mm, and may also be within the range of any two of the values exemplified here. The number of twists can be 75 to 1050 twists / m, specifically, for example, 75, 100, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1050 twists / m, and may be within the range of any two of the values exemplified here. The twisted yarn according to the present invention has excellent strength and luster, and can be dyed in the same way as ordinary yarn. Furthermore, the twisted yarn can be used in the manufacture of woven fabrics (textiles), knitted fabrics, and piles for floor coverings, and can be used in the manufacture of cloth, artificial turf coverings, floor coverings, etc. A textile and a fabric obtained by processing the textile according to one embodiment of the present invention have excellent strength and gloss and can be used for wallpaper, canvas for oil paintings, tatami mats, rush mats, sportswear for karate, yukata sashes, shirts, work clothes, handkerchiefs, towels, curtains, etc. [Examples]
[0092] The features of the present invention will be further described below with reference to examples and comparative examples. The materials, amounts used, proportions, processing content, and processing procedures shown in the following examples can be modified as appropriate without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the following specific examples.
[0093] <Manufacturing Example 1> (Manufacturing of phosphated pulp) (Phosphorus oxo-oxidation treatment) The raw material pulp used is hardwood pulp manufactured by Oji Paper Co., Ltd. (solids content 93% by mass, basis weight 245 g / m²). 2 A sheet-like material with a Canadian standard filtration efficiency (CSF) of 700 ml (measured according to JIS P 8121-2:2012) was used. The raw pulp was subjected to phosphorylation treatment as follows. First, a mixed aqueous solution of ammonium dihydrogen phosphate and urea was added to 100 parts by mass (oven-dry mass) of the raw pulp to adjust the mixture to 45 parts by mass of ammonium dihydrogen phosphate, 120 parts by mass of urea, and 150 parts by mass of water, thereby obtaining chemically impregnated pulp. Next, the obtained chemically impregnated pulp was heated in a hot air dryer at 165°C for 250 seconds to introduce phosphate groups into the cellulose in the pulp, thereby obtaining phosphorylated pulp.
[0094] (Cleaning process) Next, the obtained phosphorylated pulp was subjected to a washing treatment. The washing treatment was carried out by repeatedly adding 10 L of deionized water to 100 g (oven-dry mass) of phosphorylated pulp to obtain a pulp dispersion, stirring the mixture to ensure uniform dispersion of the pulp, and then filtering and dewatering it. The washing was terminated when the conductivity of the filtrate fell to 100 μS / cm or less.
[0095] (Neutralization treatment) Next, the washed phosphorylated pulp was subjected to a neutralization treatment as follows. First, the washed phosphorylated pulp was diluted with 10 L of deionized water, and then a 1N sodium hydroxide aqueous solution was gradually added while stirring to obtain a phosphorylated pulp slurry with a pH of 12 to 13. Next, the phosphorylated pulp slurry was dehydrated to obtain phosphorylated pulp that had undergone neutralization treatment. Then, the phosphorylated pulp that had undergone neutralization treatment was subjected to the washing treatment described above.
[0096] (Nitrogen removal treatment) A slurry with a solid content of 4% by mass was prepared by adding deionized water to phosphorylated pulp. A 48% by mass aqueous sodium hydroxide solution was added to the slurry to adjust the pH to 13.4, and the slurry was heated at a temperature of 85°C for 1 hour. Subsequently, this pulp slurry was dehydrated, and the pulp dispersion obtained by pouring 10 L of deionized water over 100 g (dry mass) of phosphorylated pulp was stirred to ensure uniform dispersion of the pulp, and the process of filtration and dewatering was repeated to remove excess sodium hydroxide. The removal process was terminated when the electrical conductivity of the filtrate was 100 μS / cm or less. The amount of carbamide groups introduced, obtained from the nitrogen content measured by the measurement method described later, was 0.01 mmol / g.
[0097] The resulting phosphorus oxoxide pulp was subjected to infrared absorption spectroscopy using FT-IR. The result showed that at 1230 cm⁻¹ -1 Absorption based on the P=O of phosphate groups was observed in the vicinity, confirming that phosphate groups were added to the pulp. Furthermore, when the obtained phosphorylated pulp was analyzed using an X-ray diffractometer, typical peaks were observed at two locations: around 2θ = 14° to 17° and around 2θ = 22° to 23°, confirming that the cellulose type I crystal structure was maintained. The amount of phosphate groups (amount of first dissociated acid) measured by the measurement method described later was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.
[0098] (Fibration of phosphated pulp) Deionized water was added to the obtained phosphorylated pulp to prepare a slurry with a solid content of 2% by mass. This slurry was processed four times at a pressure of 200 MPa using a wet atomizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a dispersion of phosphorylated microfibrous cellulose containing phosphorylated microfibrous cellulose. The fiber width of the phosphorylated microfibrous cellulose was measured using a transmission electron microscope and was found to be 3-5 nm. The phosphorylated microfibrous cellulose obtained in Production Example 1 is referred to as fibrous cellulose 1 (corresponding to the first fibrous cellulose).
[0099] Furthermore, when the above-mentioned fibrous cellulose 1 was prepared as a 1% (w / v) aqueous dispersion, its B-type viscosity, measured at 20°C and 60 rpm, was 7140 mPa·s.
[0100] (Measurement of phosphate group content) The amount of phosphate groups was measured by adding deionized water to a dispersion of fibrous cellulose containing the target fibrous cellulose to prepare a dispersion with a fibrous cellulose content of 0.2% by mass. The obtained dispersion was then treated with an ion exchange resin and measured by titration using an alkali. The ion exchange resin treatment was performed by adding 1 / 10 the volume of strongly acidic ion exchange resin (Amberjet 1024; manufactured by Organo Corporation, conditioned) to the above-mentioned fine fibrous cellulose-containing dispersion, shaking for 1 hour, and then pouring the mixture onto a mesh with a mesh size of 90 μm to separate the ion exchange resin from the dispersion. Furthermore, the alkali titration was performed by adding 10 μL of 0.1 N sodium hydroxide aqueous solution to a dispersion containing fine fibrous cellulose after treatment with ion exchange resin, at 5-second intervals, and measuring the change in the pH value of the dispersion. In this neutralization titration, two points were observed in the curve plotting the measured pH against the amount of alkali added, where the increment (the derivative of pH with respect to the amount of alkali added) was maximum. Of these, the first increment maximum obtained after starting to add alkali is called the first endpoint, and the next increment maximum obtained is called the second endpoint (Figure 1). The amount of alkali required from the start of the titration to the first endpoint is equal to the amount of the first dissociated acid in the dispersion used for titration. Also, the amount of alkali required from the start of the titration to the second endpoint is equal to the total amount of dissociated acid in the dispersion used for titration. Furthermore, the amount of alkali (mmol) required from the start of the titration to the first endpoint was divided by the solid content (g) in the titrated dispersion to determine the amount of phosphorus oxoacid groups (mmol / g). In addition, the amount of alkali (mmol) required from the start of the titration to the second endpoint was divided by the solid content (g) in the titrated dispersion to determine the total amount of dissociated acid (mmol / g). Note that the amount of phosphorus oxoacid groups (amount of phosphorus oxoacid groups introduced) (mmol / g) indicates the amount of substituents per gram of mass of fine fibrous cellulose when the counterion of the phosphorus oxoacid group is a hydrogen ion (H+).
[0101] <Example 1> (Dilution of phosphorylated microfiber cellulose) Deionized water was added to the phosphorylated microfibrous cellulose dispersion obtained in Production Example 1 so that the solid content concentration was diluted to 0.2% by mass. An electronically controlled stirrer (EUROSTAR20, manufactured by IKA) was used as the agitator, and the mixture was stirred at 4000 rpm for 10 minutes to obtain diluted phosphorylated microfibrous cellulose dispersion 1.
[0102] (Manufacturing of base paper for processing) Manila hemp pulp (fiber diameter over 1 μm, aspect ratio 150 or higher) is the main component, with a basis weight of 15 g / m². 2 The base paper was cut to 297 x 200 mm to obtain a base paper (base paper containing second fibrous cellulose). The mass of the base paper was measured using an electronic balance (base paper mass). Phosphorylated fine fibrous cellulose dispersion diluent 1 was filled into a tray, and the base paper was immersed in the tray for 1 minute to obtain a wet paper impregnated with the phosphorylated fine fibrous cellulose dispersion diluent 1. After allowing the wet paper to stand until the diluent stopped dripping, the mass of the wet paper was measured using an electronic balance (wet paper mass). The amount of phosphorylated fine fibrous cellulose dispersion diluent 1 impregnating the base paper was obtained by subtracting the mass of the base paper from the mass of the wet paper, and the coating mass was calculated by multiplying the impregnation amount by the solid content concentration of the phosphorylated fine fibrous cellulose dispersion diluent 1. Next, the base paper was dried in a 90°C hot air dryer (DKN603, manufactured by Yamato Scientific Co., Ltd.) with both short sides of the base paper fixed, to obtain a base paper for processing. In addition, the dimensions of the base paper for processing were measured in the longitudinal (MD) and transverse (CM) directions.
[0103] <Example 2> After immersing the base paper in phosphorylated fine fibrous cellulose dispersion dilution 1, both sides of the base paper are treated with cardboard (70% recycled pulp content, basis weight 465 g / m²). 2A base paper for processing was obtained in the same manner as in Example 1, except that a squeezing process was performed to remove phosphorylated fine fibrous cellulose adsorbed on the surface of the base paper by sandwiching it between two plates and lightly rubbing it 10 times by hand. The mass of the base paper after the squeezing process was measured using an electronic balance (wet paper mass).
[0104] <Example 3> A base paper for processing was obtained in the same manner as in Example 1, except that a diluted phosphorylated microfibrous cellulose dispersion 2 was used, which was obtained by diluting the phosphorylated microfibrous cellulose dispersion to a solid content concentration of 0.5% by mass.
[0105] <Example 4> A base paper for processing was obtained in the same manner as in Example 2, except that phosphorylated fine fibrous cellulose dispersion dilution 2 was used.
[0106] <Comparative Example 1> A base paper for processing was obtained in the same manner as in Example 1, except that water was used instead of phosphorylated microfibrous cellulose dispersion diluent 1.
[0107] (evaluation) The fibrous cellulose aqueous dispersions and the base paper for processing obtained in the examples and comparative examples were evaluated by the following method.
[0108] [Viscosity measurement] Diluted phosphorylated microfibrous cellulose dispersions 1 and 2 were allowed to stand at 23°C for 17 hours, after which their viscosity (mPa·s) was measured using a B-type viscometer (LV-2T, BLOOKFIELD). The measurement was performed under conditions of 23°C, and the viscosity was measured after rotating at 3 rpm for 3 minutes.
[0109] [Tensile strength] In accordance with JIS P 8113:2006, the tensile strength (MPa) of processing base paper (test length 180 mm) with a test specimen size of 240 mm long x 15 mm wide was measured using a Tensilon tensile testing machine (RTG1310, manufactured by A&D Co., Ltd.). For the measurement, samples that had been conditioned at 23°C and 50% relative humidity for 24 hours or more were used as test specimens.
[0110] [Analysis of mass behavior in response to humidity changes (hygroscopic properties)] The base paper for processing, with test specimen sizes of 280-300 mm x 180-200 mm, obtained in Examples 1-4 and Comparative Example 1, was thoroughly humidified by standing at 23°C and 50% relative humidity for 24 hours or more. The mass M0 (g) of the base paper at that time was measured using an electronic balance. Next, the base paper for processing was exposed to a constant temperature and humidity chamber (KCL2000W, manufactured by EYELA) set to 23°C and 90% relative humidity for 4 hours. After that, the base paper for processing was moved back to an environment of 23°C and 50% relative humidity, and the mass M1 (g) after standing for 1 minute and the mass M10 (g) after standing for 10 minutes were measured.
[0111] [Evaluation of glossiness] For the base paper for processing obtained in Examples 1-4 and Comparative Example 1, with test specimen sizes of 280-300 mm x 180-200 mm, light was shone from a light source (model P7R, manufactured by Ledlenser) placed at a distance of 10-15 cm, and the glossiness was evaluated from the reflected light. A: It's glowing all over. B: Partially glowing C: Not glowing
[0112] [Table 1]
Claims
1. A base paper for processing containing fibrous cellulose, wherein the fibrous cellulose includes first fibrous cellulose with a fiber diameter of 100 μm or less. A base paper for processing in which the ratio M1 / M0 of the mass M0 of the base paper for processing at 23°C and 50% relative humidity, measured by the measurement method described below, to the mass M1 after the base paper for processing has been conditioned at 23°C and 90% relative humidity, then moved to 23°C and 50% relative humidity and left to stand for 60 seconds, is 1.060 or more. (Measurement method) - Cut the aforementioned base paper for processing and prepare test base paper for processing. - The mass of the test processing base paper after it has been conditioned in an environment of 23°C and 50% relative humidity is defined as M0 (g). - The test processing base paper, which has been conditioned at 23°C and 50% relative humidity, is left to stand for 4 hours in an environment of 23°C and 90% relative humidity. Then, it is moved to an environment of 23°C and 50% relative humidity, and its mass after standing for 60 seconds is taken as M1 (g).
2. The base paper for processing according to claim 1, A base paper for processing in which the ratio M10 / M0 of the mass M0 of the base paper for processing at 23°C and 50% relative humidity, measured by the measurement method described below, to the mass M10 after the base paper for processing has been conditioned at 23°C and 90% relative humidity, then moved to 23°C and 50% relative humidity and left to stand for 600 seconds, is 1.040 or more. (Measurement method) - Cut the aforementioned base paper for processing and prepare test base paper for processing. - The mass of the test processing base paper after it has been conditioned in an environment of 23°C and 50% relative humidity is defined as M0 (g). - The test processing base paper, which has been conditioned at 23°C and 50% relative humidity, is left to stand for 4 hours in an environment of 23°C and 90% relative humidity. Then, it is moved to an environment of 23°C and 50% relative humidity, and its mass after standing for 600 seconds is defined as M10 (g).
3. A base paper for processing according to claim 1 or claim 2, A base paper for processing, having a tensile strength of 37.00 MPa or higher as measured according to JIS P 8113.
4. A base paper for processing according to claim 1 or claim 2, wherein the fibrous cellulose includes a second fibrous cellulose, The second fibrous cellulose is a base paper for processing, different from the first fibrous cellulose.
5. A base paper for processing according to claim 1 or claim 2, The first fibrous cellulose comprises a fibrous cellulose having one or more substituents selected from the group consisting of a phosphorus oxoacid group or substituents derived from a phosphorus oxoacid group, a carboxyl group or substituents derived from a carboxyl group, a sulfur oxoacid group or substituents derived from a sulfur oxoacid group, a xantate group or substituents derived from a xantate group, a phosphonone group or substituents derived from a phosphonone group, a phosphine group or substituents derived from a phosphine group, a sulfone group or substituents derived from a sulfone group, and a carboxyalkyl group, and is used as a base paper for processing.
6. A base paper for processing according to claim 1 or claim 2, which is used as a base paper for paper yarn.
7. A base paper for paper yarn, comprising the base paper for processing described in claim 1 or claim 2.
8. A twisted yarn obtained by processing the paper yarn base described in claim 7.
9. A textile obtained by processing the twisted yarn described in claim 8.
10. A pile for carpets, made by processing the twisted yarn described in claim 8.
11. A pile for floor covering according to claim 10, which is used as the pile portion of an artificial turf installation or floor covering.
12. A fabric obtained by processing the textile described in claim 9.
13. A method for manufacturing base paper for processing, comprising an immersion step and a drying step, In the immersion step, a paper substrate containing a second fibrous cellulose is immersed in a dispersion containing a first fibrous cellulose with a fiber diameter of 100 μm or less to obtain wet paper. In the drying step, the wet paper is dried to obtain base paper for processing. Manufacturing method.
14. A manufacturing method according to claim 13, The first fibrous cellulose is manufactured in which the B-type viscosity measured at 20°C and 60 rpm in a 1% (w / v) aqueous dispersion is greater than 7000 mPa·s.
15. A manufacturing method according to claim 13 or claim 14, A method for producing the first fibrous cellulose, comprising fibrous cellulose having one or more substituents selected from the group consisting of a phosphorus oxoacid group or substituents derived from a phosphorus oxoacid group, a carboxyl group or substituents derived from a carboxyl group, a sulfur oxoacid group or substituents derived from a sulfur oxoacid group, a xantate group or substituents derived from a xantate group, a phosphonone group or substituents derived from a phosphonone group, a phosphine group or substituents derived from a phosphine group, a sulfone group or substituents derived from a sulfone group, and a carboxyalkyl group.
16. A base paper for processing containing fibrous cellulose, wherein the fibrous cellulose comprises first fibrous cellulose and second fibrous cellulose. The first fibrous cellulose has a fiber diameter of 100 μm or less. The base paper for processing is obtained by immersing a paper substrate containing the second fibrous cellulose in a dispersion containing the first fibrous cellulose to obtain wet paper, and then drying the wet paper.
Citation Information
Patent Citations
Base paper for paper yarn
JP2012087431A